Sacred Texts Produced under the Shadows of Empires - Hulisani Ramantswana (Old Testament Essays, 2023)
The Hebrew Bible is a complex of sacred texts shaped and reshaped by Israelites, Judaeans and later Jews under the shadows of empires, which threatened, oppressed, dominated and at times provided protection to them. At the same time, they more often than not had to resist, shun, and yet forcefully submit to the empire and on other occasions, they supported, colluded with and mimicked the empire. This essay explores decolonial options for reading the Hebrew Bible, considering two determinations: the Hebrew Bible is a product of the colonised and was influenced and sponsored by the empire.